Why factor XI deficiency is a clinical concern. Issue 7 (2nd July 2016) - Wheeler, Allison P.; Gailani, David
ABSTRACT: Introduction : Inherited fXI deficiency has been an enigma since its discovery in 1953. The variable and relatively mild symptoms in patients with even the most severe form of the disorder seem out of step with the marked abnormalities in standard clotting assays. Indeed, the contribution of factor XI to hemostasis in an individual is not adequately assessed by techniques available in modern clinical laboratories. Areas covered : We discuss clinical studies, genetic/genomic analyses, and advances in laboratory medicine that are reshaping our views on the role of factor XI in pathologic coagulation. We review how the disorder associated with factor XI deficiency has contributed to changes in blood coagulation models, and discuss the complex genetics of the deficiency state and its relationship to bleeding. Finally, we cover new laboratory approaches that may distinguish deficient patients who are prone to bleeding from those without such predisposition. Expert commentary : Advances in understanding the biology of factor XI have led to modifications in treatment of factor XI-deficient patients. Factor replacement is used more judiciously, and alternative approaches are gaining favor. In the future, better laboratory tests may allow us to target therapy to those patients who would benefit most.